Massive Gene Transfer and Extensive RNA Editing of a Symbiotic Dinoflagellate Plastid Genome - Mungpakdee, Sutada; Shinzato, Chuya; Takeuchi, Takeshi; Kawashima, Takeshi; Koyanagi, Ryo; Hisata, Kanako; Tanaka, Makiko; Goto, Hiroki; Fujie, Manabu; Lin, Senjie; Satoh, Nori; Shoguchi, Eiichi (Genome biology and evolution, 2014)
Genome sequencing of Symbiodinium minutum revealed that 95 of 109 plastid-associated genes have been transferred to the nuclear genome and subsequently expanded by gene duplication. Only 14 genes remain in plastids and occur as DNA minicircles. Each minicircle (1.8–3.3 kb) contains one gene and a conserved noncoding region containing putative promoters and RNA-binding sites. Nine types of RNA editing, including a novel G/U type, were discovered in minicircle transcripts but not in genes transferred to the nucleus. In contrast to DNA editing sites in dinoflagellate mitochondria, which tend to be highly conserved across all taxa, editing sites employed in DNA minicircles are highly variable from species to species. Editing is crucial for core photosystem protein function. It restores evolutionarily conserved amino acids and increases peptidyl hydropathy. It also increases protein plasticity necessary to initiate photosystem complex assembly.